Separator for power storage device and power storage device

A polypropylene-based separator with controlled pore diameters in its microporous layers addresses clogging and thermal stability issues, enhancing the performance and longevity of power storage devices.

JP7620113B2Active Publication Date: 2025-01-22CELGARD LLC +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023540155
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-29
Filing Date
2022-03-14
Publication Date
2025-01-22
Estimated Expiration
2042-03-14

AI Technical Summary

Technical Problem

The separator in power storage devices is prone to clogging due to deposits during cycle deterioration, and there is a need for separators with excellent air permeability and dimensional stability, especially at high temperatures, as batteries increase in size.

Method used

A separator composed of a base material with microporous layers containing 70% by mass of polypropylene, where the area average long pore diameter is carefully controlled to suppress clogging and enhance thermal stability, with specific layers having different pore diameters to manage clogging and short circuits effectively.

Benefits of technology

The proposed separator effectively reduces clogging and maintains excellent thermal stability, ensuring good battery performance even at high temperatures, thereby extending the cycle life and preventing short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620113000001
    Figure 0007620113000001
  • Figure 0007620113000002
    Figure 0007620113000002
  • Figure 0007620113000003
    Figure 0007620113000003
Patent Text Reader

Abstract

The present disclosure provides a separator for an electricity storage device that is inhibited from clogging and has excellent thermal stability, and an electricity storage device using the same. [Solution] The separator for an electricity storage device has a microporous layer (A) and a microporous layer (B) containing 70 mass% or more of polypropylene, and the area average long pore diameter in the ND-MD cross section of the microporous layer (B) is 0.95 times or less the area average long pore diameter in the ND-MD cross section of the microporous layer (A). Alternatively, the separator for an electricity storage device contains 70 mass% or more of polyolefin, and the area average long pore diameter of a first porous surface (X) is 1.05 to 10 times the area average long pore diameter of a second porous surface (Y) on the opposite side.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a separator for an electricity storage device and an electricity storage device. [Background technology]

[0002] Microporous membranes, particularly polyolefin-based microporous membranes, are used in many technical fields such as microfiltration membranes, battery separators, condenser separators, fuel cell materials, etc., and are particularly used as separators for secondary batteries such as lithium-ion batteries. Lithium-ion batteries are used in various applications such as small electronic devices such as mobile phones and notebook personal computers, as well as electric vehicles including hybrid automobiles and plug-in hybrid automobiles.

[0003] In recent years, there has been a demand for lithium ion batteries having high energy capacity, high energy density, and high output characteristics. Accordingly, there is an increasing demand for thin separators that have excellent battery performance, reliability, and safety.

[0004] For example, US Patent No. 5,999,943 describes multilayer microporous thin films or membranes that may exhibit improved properties, including improved dielectric breakdown and strength, compared to conventional single-layer or triple-layer microporous membranes of the same thickness. A preferred multilayer microporous membrane includes a microlayer and one or more stacked barriers.

[0005] Patent Document 2 describes a separator for an electricity storage device having a microporous membrane mainly composed of polyolefin, the microporous membrane having a melt tension of 30 mN or less when measured at a temperature of 230°C, and a melt flow rate (MFR) of 0.9 g / 10 min or less when measured under a load of 2.16 kg at a temperature of 230°C. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 089748 [Patent Document 2] International Publication No. 2020 / 196120 Summary of the Invention [Problem to be solved by the invention]

[0007] There is a problem that the deposits generated by cycle deterioration cause clogging of the separator, resulting in a decrease in cycle life. In addition, as batteries become larger, there is a demand for separators that are excellent in air permeability and dimensional stability even after being exposed to high temperatures.

[0008] Therefore, an object of the present disclosure is to provide a separator for an electricity storage device that is suppressed from clogging and has excellent thermal stability, and an electricity storage device using the same. [Means for solving the problem]

[0009] Examples of embodiments of the present disclosure are listed in the following items [1] to

[22] . [1] A substrate having a microporous layer (A) containing 70% by mass or more of polypropylene and a microporous layer (B) containing 70% by mass or more of polypropylene, A separator for an electricity storage device, wherein the area average long pore diameter of the pores in the microporous layer (B) in the ND-MD cross section is 0.95 times or less the area average long pore diameter of the pores in the microporous layer (A) in the ND-MD cross section. [2] Item 2. The separator for an electricity storage device according to item 1, wherein the area average pore diameter of the pores in the microporous layer (B) in the ND-MD cross section is 0.30 to 0.90 times the area average pore diameter of the pores in the microporous layer (A) in the ND-MD cross section. [3] 3. The separator for an electricity storage device according to item 1 or 2, wherein the base material has an air permeability change rate of 100% or less when heated at 140° C. for 30 minutes in air with its ends restrained. [4] 4. The separator for an electricity storage device according to any one of items 1 to 3, wherein the area average long pore diameter of the pores in the microporous layer (A) in the ND-MD cross section is 100 nm or more and 600 nm or less. [5] 5. The separator for an electricity storage device according to any one of items 1 to 4, wherein the microporous layers (A) constitute the outermost layers on both sides of the substrate. [6] 6. The separator for an electricity storage device according to any one of items 1 to 5, wherein the substrate further has a microporous layer (C) containing 50% by mass or more of a polyolefin. [7] Item 7. The separator for an electricity storage device according to item 6, wherein the area average pore diameter of the pores in the microporous layer (C) in the ND-MD cross section is 0.20 to 0.90 times the area average pore diameter of the pores in the microporous layer (B) in the ND-MD cross section. [8] 8. The separator for an electricity storage device according to item 6 or 7, wherein the substrate has a structure in which a microporous layer (A), a microporous layer (B), and a microporous layer (C) are laminated in this order. [9] 9. The separator for an electricity storage device according to any one of items 1 to 8, wherein the substrate has a structure in which a microporous layer (A), a microporous layer (B), and a microporous layer (A) are laminated in this order.

[10] The surface of the substrate facing the microporous layer (A) is designated as a first porous surface (X), and the surface opposite to the first porous surface (X) is designated as a second porous surface (Y). The area average long pore diameter (S X ) is the area average long pore diameter (S Y 9. The separator for an electricity storage device according to any one of items 1 to 8, wherein the average molecular weight of the separator is from 1.05 to 10 times the molecular weight of the separator.

[11] The average long hole diameter (S X 11. The separator for an electricity storage device according to item 10, wherein the thickness of the first insulating film is 80 nm or more and 600 nm or less.

[12] 12. The separator for an electricity storage device according to any one of items 1 to 11, wherein the substrate has a thermal shrinkage rate in the width direction after heating at 150° C. for 1 hour of −1.0% or more and 3.0% or less.

[13] 13. An electricity storage device comprising a positive electrode, a negative electrode, and the separator for an electricity storage device according to any one of items 1 to 12.

[14] Item 14. The electricity storage device according to item 13, wherein the microporous layer (A) is disposed facing a negative electrode.

[15] Item 15. The power storage device according to item 13 or 14, wherein the positive electrode contains lithium iron phosphate as a positive electrode active material.

[16] A substrate containing 70% by weight or more of polyolefin and having a first porous surface (X) and a second porous surface (Y) opposite to the first porous surface (X), The area average long pore diameter (S X ) is the area average long pore diameter (S Y ) is 1.05 to 10 times the

[17] The average long hole diameter (S X Item 17. The separator for an electricity storage device according to item 16, wherein the thickness of the first insulating film is 80 nm or more and 600 nm or less.

[18] Item 18. The separator for use in an electricity storage device according to item 16 or 17, wherein the polyolefin is polypropylene.

[19] 19. The separator for an electricity storage device according to any one of items 16 to 18, wherein the substrate has a thermal shrinkage rate in the width direction after heating at 150° C. for 1 hour of −1.0% or more and 3.0% or less.

[20] 20. An electricity storage device comprising a positive electrode, a negative electrode, and the separator for an electricity storage device according to any one of items 16 to 19. [twenty one] 21. The electricity storage device according to item 20, wherein the first porous surface (X) is disposed facing the negative electrode side. [twenty two] 22. The power storage device according to item 20 or 21, wherein the positive electrode contains lithium iron phosphate as a positive electrode active material. [twenty three] A substrate having a microporous layer (A) containing 70% by mass or more of polypropylene and a microporous layer (B) containing 70% by mass or more of polypropylene, A microporous membrane, in which the area average long pore diameter of the pores in the microporous layer (B) in the ND-MD cross section is 0.95 times or less the area average long pore diameter of the pores in the microporous layer (A) in the ND-MD cross section. Effect of the Invention

[0010] According to the present disclosure, there are provided a separator for an electricity storage device which is suppressed from clogging and has excellent thermal stability, and an electricity storage device using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <Separator for power storage device> The separator for an electric storage device of the present disclosure has a substrate having a microporous layer containing 70% by mass or more of polyolefin. The polyolefin is preferably polypropylene. The substrate may be composed of a single (single) microporous layer containing 70% by mass or more of polypropylene, or may have a microporous layer (A) containing 70% by mass or more of polypropylene and a microporous layer (B) containing 70% by mass or more of polypropylene. The substrate may further have a coating layer (also called a "surface layer", a "coating layer", etc., hereinafter simply referred to as a "coating layer") on one or both sides. In this specification, the "microporous layer" means each microporous layer constituting the substrate of the separator, the "substrate" means the substrate of the separator excluding any coating layer, and the "separator" means the entire separator including any coating layer. It is preferable that the substrate does not have a layer containing 50% by mass or more of polyethylene.

[0012] <Microporous layer (A)> The separator for an electric storage device of the present disclosure preferably has a microporous layer (A) containing 70% by mass or more of polypropylene. The separator for an electric storage device may have only one microporous layer (A) or two or more layers. At least one of the microporous layers (A) constitutes the outermost layer on at least one side of the substrate. When the separator for an electric storage device has two or more microporous layers (A), the microporous layer (A) may constitute the outermost layer on both sides of the substrate. The microporous layer (A) contains 70% by mass or more of polypropylene, which allows the battery to maintain good battery performance even after storage at high temperature (140°C). The lower limit of the polypropylene content in the microporous layer (A) is 70% by mass or more, preferably 75% by mass or more, 80% by mass or more, 85% by mass or more, or 90% by mass or more, from the viewpoints of the wettability, thinning, and shutdown characteristics of the separator. The upper limit of the polypropylene content in the microporous layer (A), which can be combined with these lower limits, is not limited, and may be, for example, 80% by mass or less, 90% by mass or less, 95% by mass or less, 98% by mass or less, or 99% by mass or less, or may be 100% by mass.

[0013] <Material for the microporous layer (A)> The microporous layer (A) contains 70% by mass or more of polypropylene. The polypropylene of the microporous layer (A) may be the same material as the polypropylene of the microporous layer (B) and the microporous layer (C) described later, or may be a polypropylene having a different chemical structure, more specifically, a polypropylene having at least one different monomer composition, stereoregularity, molecular weight, crystal structure, etc.

[0014] The stereoregularity of the polypropylene is not limited, but may be, for example, an atactic, isotactic, or syndiotactic homopolymer, etc. The polypropylene according to the present disclosure is preferably an isotactic or syndiotactic highly crystalline homopolymer.

[0015] The polypropylene of the microporous layer (A) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of comonomer other than propylene, such as an α-olefin comonomer, is copolymerized. The amount of propylene structure contained as a repeating unit in the polypropylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The amount of repeating units of the comonomer is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polypropylene may be used alone or in combination of two or more kinds.

[0016] The weight average molecular weight (Mw) of the polypropylene of the microporous layer (A) is preferably 300,000 or more from the viewpoint of the strength of the microporous layer, etc., and is preferably 1,500,000 or less from the viewpoint of increasing the pore size of the microporous layer and avoiding clogging. The Mw of the polypropylene is more preferably 500,000 or more and 1,300,000 or less, even more preferably 600,000 or more and 1,100,000 or less, still more preferably 700,000 or more and 1,050,000 or less, and particularly preferably 800,000 or more and 1,000,000 or less.

[0017] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polypropylene of the microporous layer (A) by the number average molecular weight (Mn) is preferably 7 or less, more preferably 6.5 or less, 6 or less, 5.5 or less, or 5 or less. The smaller the Mw / Mn value of the polypropylene, the smaller the melt tension of the obtained microporous layer (A) becomes, and the pore size tends to be larger than that of the microporous layer (B). The lower limit of the Mw / Mn, which can be combined with these upper limits, is preferably 1 or more, for example, 1.3 or more, 1.5 or more, 2.0 or more, or 2.5 or more. By having Mw / Mn of 1 or more, appropriate molecular entanglement is maintained, and stability during film formation may be improved. The weight average molecular weight, number average molecular weight, and Mw / Mn of the polyolefin of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement.

[0018] The density of the polypropylene of the microporous layer (A) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The upper limit of the density of the polypropylene, which can be combined with these lower limits, is preferably 1.1 g / cm 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polyolefins is related to the crystallinity of polypropylene, and the density of polypropylene can be less than 0.85 g / cm 3 By setting the above amount, the productivity of the microporous layer is improved, which is particularly advantageous in the dry method.

[0019] The microporous layer (A) may contain other resins as long as it contains 70% by mass or more of polypropylene. Examples of other resins include polyolefins other than polypropylene (also referred to as "other polyolefins") and copolymers of polystyrene and polyolefins. Polyolefins are polymers containing a monomer having a carbon-carbon double bond as a repeating unit. Monomers constituting polyolefins other than polypropylene are not limited, but include monomers having 2 or 4 to 10 carbon atoms and having a carbon-carbon double bond, such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Polyolefins are, for example, homopolymers, copolymers, or multi-stage polymerization polymers, and are preferably homopolymers. Specifically, polyethylene is preferred as the polyolefin from the viewpoint of shutdown characteristics and the like. Preferred examples of the copolymers of polystyrene and polyolefins include styrene-(ethylene-propylene)-styrene copolymers (SEPS), styrene-(ethylene-butene)-styrene copolymers, and styrene-ethylene-styrene copolymers. Particularly preferred is a styrene-(ethylene-propylene)-styrene copolymer (SEPS).

[0020] The weight average molecular weight (Mw) of the other polyolefin is preferably 300,000 or more from the viewpoint of the strength of the microporous layer, etc., and is preferably 1,500,000 or less from the viewpoint of increasing the pore size of the microporous layer to avoid clogging and obtain high output. The Mw of the polyolefin is more preferably 500,000 or more and 1,300,000 or less, even more preferably 600,000 or more and 1,100,000 or less, still more preferably 700,000 or more and 1,000,000 or less, and particularly preferably 800,000 or more and 960,000 or less.

[0021] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the other polyolefin by the number average molecular weight (Mn) is preferably 7 or less, more preferably 6.5 or less, 6 or less, 5.5 or less, or 5 or less. The lower limit of Mw / Mn of the polyolefin of the microporous layer (A), which can be combined with these upper limits, is preferably 1 or more, for example, 1.3 or more, 1.5 or more, 2.0 or more, or 2.5 or more. By having Mw / Mn of 1 or more, appropriate molecular entanglement is maintained, and stability during film formation may be improved.

[0022] <Melt flow rate (MFR) of microporous layer (A)> The upper limit of the melt flow rate (MFR) of the microporous layer (A) (MFR of a single layer) is preferably 4.0 g / 10 min or less from the viewpoint of obtaining a microporous layer (A) with higher strength, and may be, for example, 3.0 g / 10 min or less, 2.0 g / 10 min or less, 1.5 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the microporous layer (A) (MFR of a single layer) that can be combined with these upper limits is not limited from the viewpoint of the moldability of the microporous layer (A), and may be, for example, 0.3 g / 10 min or more, 0.35 g / 10 min or more, 0.4 g / 10 min or more, 0.45 g / 10 min or more, or 0.5 g / 10 min or more. The MFR of the microporous layer (A) is measured under conditions of a load of 2.16 kg and a temperature of 230°C.

[0023] The MFR of the microporous layer (A) being 4.0 g / 10 min or less means that the molecular weight of the polyolefin contained in the microporous layer (A) is relatively high. The high molecular weight of the polyolefin increases the number of tie molecules that bond the crystalline substances together, and therefore the microporous layer (A) tends to have high strength. The MFR of the microporous layer (A) being 0.3 g / 10 min or more is preferable because it reduces the melt tension during the formation of the microporous layer (A) and allows the pore size of the microporous layer (A) to be larger than that of the microporous layer (B).

[0024] From the viewpoint of obtaining a high-strength microporous layer (A), the MFR of the polypropylene of the microporous layer (A) is preferably 0.3 to 4.0 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 230° C. From the viewpoint of obtaining a microporous layer with higher strength, the upper limit of the MFR of the polypropylene may be, for example, 3.0 g / 10 min or less, 2.0 g / 10 min or less, 1.5 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the polypropylene that can be combined with these upper limits is not limited, but from the viewpoint of moldability of the microporous layer (A), it may be, for example, 0.3 g / 10 min or more, 0.35 g / 10 min or more, 0.4 g / 10 min or more, or 0.45 g / 10 min or more.

[0025] <Pentad fraction of microporous layer (A)> The lower limit of the pentad fraction of the polypropylene of the microporous layer (A) is preferably 94.0% or more, for example, 95.0% or more, 96.0% or more, 96.5% or more, 97.0% or more, 97.5% or more, 98.0% or more, 98.5% or more, or 99.0% or more, from the viewpoint of obtaining a microporous layer with low air permeability. The upper limit of the pentad fraction of the polypropylene that can be combined with these lower limits is not limited, but may be 99.9% or less, 99.8% or less, or 99.5% or less. The pentad fraction of the polypropylene is 13 Measured by C-NMR (nuclear magnetic resonance).

[0026] A pentad fraction of 94.0% or more of polypropylene indicates high crystallinity of the polypropylene. In separators obtained by the stretching perforation method, particularly the dry method, the amorphous parts between the crystalline parts are stretched to form pores, so if the polypropylene has high crystallinity, the pores become good and the air permeability can be kept low, which enables the battery to have high output.

[0027] <Area-average long pore diameter of the microporous layer (A)> The area average long pore diameter (hereinafter, simply referred to as "area average long pore diameter") of the microporous layer (A) in the ND-MD cross section is preferably larger than the area average long pore diameter of the microporous layer (B). The area average long pore diameter of the microporous layer (B) is preferably 0.99 times or less the area average long pore diameter of the microporous layer (A). In the present specification, "ND" indicates the thickness direction of the microporous layer, and "MD" indicates the film formation direction of the microporous layer. For example, the MD of a separator having a microporous layer is the longitudinal direction if it is a roll. "Long pore diameter" means the pore diameter in MD. In addition, when there are two or more microporous layers (A) and / or microporous layers (B), the area average long pore diameters of the microporous layer (A) and the microporous layer (B) are compared based on the average area average long pore diameter value of each layer.

[0028] The area average long pore diameter of the microporous layer (B) is 0.99 times or less than the area average long pore diameter of the microporous layer (A), which means that the microporous layer (A) which is the outermost layer of the substrate is a microporous layer having a larger pore diameter than the microporous layer (B). When the area average long pore diameter of the microporous layer (B) is 0.99 times or less than that of the microporous layer (A), clogging reduction and short circuit suppression can be achieved at the same time. More specifically, it is considered that the clogging of the separator caused by deposits in battery evaluation (cycle test) can be reduced by the microporous layer (A) which is the outermost layer having a large pore diameter, and that the short circuit in the electricity storage device can be suppressed by the microporous layer (B) which is located in the inner layer having a small pore diameter. Preferably, the area average long pore diameter of the microporous layer (B) is preferably 0.95 times or less, more preferably 0.90 times or less, of the area average long pore diameter of the microporous layer (A). As a lower limit that can be combined with these upper limits, the area average long pore diameter of the microporous layer (B) is preferably 0.30 times or more, more preferably 0.40 times or more, the area average long pore diameter of the microporous layer (A). By setting it to 0.30 times or more, it is believed that the strength of the separator can be sufficiently ensured.

[0029] The area average long pore diameter of the microporous layer (A) is preferably 100 nm or more and 600 nm or less. When the area average long pore diameter of the microporous layer (A) is 100 nm or more, clogging of the separator caused by deposits in the power storage device can be more effectively reduced, and when it is 600 nm or less, the strength of the separator can be further improved. In a preferred embodiment, it is more important to reduce clogging caused by deposits in the power storage device, and for this purpose, it is more important that the area average long pore diameter of the microporous layer (A) is 100 nm or more. The area average long pore diameter of the microporous layer (A) is more preferably 150 nm or more and 550 nm or less, even more preferably 180 nm or more and 500 nm or less, and even more preferably 200 nm or more and 450 nm or less.

[0030] The area-average pore size can be measured by performing cross-sectional SEM observation of the MD-ND cross section of the separator, and analyzing the image obtained in a range of 20 μm in MD × 3 μm in ND direction. Detailed conditions are shown in the Examples. When measuring the average pore size from the cross-sectional SEM image, the number-average pore size and the area-average pore size can be calculated, but the number-average pore size counts even very small pores as one pore, making it difficult to obtain a sufficient correlation with the physical properties of the separator. Therefore, in order to obtain a better correlation with the physical properties of the separator, the area-average pore size is used as the average pore size in this specification.

[0031] <Porosity of microporous layer (A)> The porosity of the microporous layer (A) is preferably 20% or more from the viewpoint of avoiding clogging in the electricity storage device and obtaining good air permeability of the separator, and is preferably 70% or less from the viewpoint of maintaining the strength of the separator. The porosity of the microporous layer (A) is more preferably 25% or more and 65% or less, further preferably 30% or more and 60% or less, and particularly preferably 35% or more and 55% or less.

[0032] <Thickness of microporous layer (A)> The thickness of the microporous layer (A) may be preferably 10 μm or less, for example, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4.5 μm or less, or 4 μm or less, from the viewpoint of increasing the energy density of the electricity storage device, etc. The lower limit of the thickness of the microporous layer (A) which can be combined with these upper limits may be preferably 1 μm or more, for example, 2 μm or more, 3 μm or more, or 3.5 μm or more, from the viewpoint of strength, etc.

[0033] Additives for the microporous layer (A) The microporous layer (A) containing 70% by mass or more of polypropylene may further contain, in addition to polypropylene, additives such as elastomers, crystal nucleating agents, antioxidants, fillers, etc., as necessary. The amount of the additives is not particularly limited, but is, for example, 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more based on the total mass of the microporous layer (A), and the upper limit of the amount of the additives that can be combined with these lower limits may be 20% by mass or less, 10% by mass or less, or 7% by mass or less.

[0034] <Microporous layer (B)> The separator for an electric storage device of the present disclosure has a microporous layer (B). The separator for an electric storage device may have only one microporous layer (B) or two or more layers. The microporous layer (B) also contains 70% by mass or more of polypropylene, which allows good battery performance to be maintained even after storage at high temperature (140°C). The lower limit of the polypropylene content in the microporous layer (B) may be preferably 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more from the viewpoints of the wettability, thinning, and shutdown characteristics of the separator. The upper limit of the polypropylene content in the microporous layer (B) that can be combined with these lower limits is not limited, and may be, for example, 80% by mass or less, 90% by mass or less, 95% by mass or less, 98% by mass or less, or 99% by mass or less, or 100% by mass.

[0035] <Material for the microporous layer (B)> The microporous layer (B) contains 70% by mass or more of polypropylene. The polypropylene of the microporous layer (B) may be the same material as the polypropylene of the microporous layer (A) and the microporous layer (C) described later, or may be a polypropylene having a different chemical structure, more specifically, a polypropylene having at least one different monomer composition, stereoregularity, molecular weight, crystal structure, etc.

[0036] The stereoregularity of the polypropylene of the microporous layer (B) is not limited, but may be, for example, atactic, isotactic, or syndiotactic homopolymer, etc. The polypropylene according to the present disclosure is preferably an isotactic or syndiotactic highly crystalline homopolymer.

[0037] The polypropylene of the microporous layer (B) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of a comonomer other than propylene, such as an α-olefin comonomer, is copolymerized. The amount of propylene structure contained as a repeating unit in the polypropylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The upper limit of the amount of the repeating unit of the comonomer is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polypropylene may be used alone or in combination of two or more kinds.

[0038] The weight average molecular weight (Mw) of the polypropylene of the microporous layer (B) is preferably 300,000 or more from the viewpoint of the strength of the microporous layer, etc., and is preferably 1,500,000 or less from the viewpoint of increasing the pore size of the microporous layer and avoiding clogging. The Mw of the polypropylene is more preferably 500,000 or more and 1,300,000 or less, even more preferably 600,000 or more and 1,100,000 or less, still more preferably 700,000 or more and 1,050,000 or less, and particularly preferably 800,000 or more and 1,000,000 or less.

[0039] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polypropylene of the microporous layer (B) by the number average molecular weight (Mn) is preferably 20 or less, more preferably 15 or less, and the lower limit that can be combined with these upper limits may be preferably 4 or more, for example 4.5 or more, 5.0 or more, 5.5 or more. The larger the Mw / Mn value of the polypropylene, the higher the melt tension of the resulting microporous layer tends to be. Therefore, it is preferable that the Mw / Mn value of the polypropylene is 4 or more, since the melt tension of the microporous layer (B) can be controlled to be larger than that of the microporous layer (A), and as a result, the pore size of the microporous layer (B) can be controlled to be smaller than that of the microporous layer (A). The weight average molecular weight, number average molecular weight, and Mw / Mn of the polyolefin of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement.

[0040] The density of the polypropylene of the microporous layer (B) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The upper limit of the density of the polypropylene, which can be combined with these lower limits, is preferably 1.1 g / cm 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polyolefins is related to the crystallinity of polypropylene, and the density of polypropylene can be less than 0.85 g / cm 3 By setting the above amount, the productivity of the microporous layer is improved, which is particularly advantageous in the dry method.

[0041] The microporous layer (B) may contain other resins as long as it contains 70% by mass or more of polypropylene. Examples of other resins include polyolefins other than polypropylene (also referred to as "other polyolefins"). Polyolefins are polymers containing a monomer having a carbon-carbon double bond as a repeating unit. Monomers constituting polyolefins other than polypropylene are not limited, but include monomers having 2 or 4 to 10 carbon atoms and having a carbon-carbon double bond, such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Polyolefins are, for example, homopolymers, copolymers, or multi-stage polymerization polymers, and are preferably homopolymers. Specifically, polyethylene is preferred as the polyolefin from the viewpoint of shutdown characteristics and the like.

[0042] <Melt flow rate (MFR) of microporous layer (B)> The upper limit of the melt flow rate (MFR) of the microporous layer (B) (MFR of a single layer) is preferably 1.5 g / 10 min or less from the viewpoint of obtaining a microporous layer (B) with higher strength, and may be, for example, 1.4 g / 10 min or less, 1.3 g / 10 min or less, 1.2 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the microporous layer (B) (MFR of a single layer) that can be combined with these upper limits is not limited from the viewpoint of the moldability of the microporous layer (B), and may be, for example, 0.2 g / 10 min or more, 0.25 g / 10 min or more, 0.3 g / 10 min or more, 0.35 g / 10 min or more, or 0.4 g / 10 min or more. The MFR of the microporous layer (B) is measured under conditions of a load of 2.16 kg and a temperature of 230°C.

[0043] The MFR of the microporous layer (B) being 1.5 g / 10 min or less means that the molecular weight of the polyolefin contained in the microporous layer (B) is relatively high. A high molecular weight polyolefin tends to produce a high-strength microporous layer (B) because of the increased number of tie molecules that bond crystalline substances together, and the melt tension can be maintained high, making it easier to control the pore size to a small size. The MFR of the microporous layer (B) being 0.2 g / 10 min or more ensures that the melt tension of the microporous layer (B) does not become too low, making it easier to produce a high-strength, thin-film microporous layer.

[0044] From the viewpoint of obtaining a high-strength microporous layer (B), the MFR of the polypropylene of the microporous layer (B) is preferably 0.2 to 1.5 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 230° C. From the viewpoint of obtaining a microporous layer with higher strength, the upper limit of the MFR of the polypropylene may be, for example, 1.4 g / 10 min or less, 1.3 g / 10 min or less, 1.2 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the polypropylene that can be combined with these upper limits is not limited, but from the viewpoint of moldability of the microporous layer (B), it may be, for example, 0.25 g / 10 min or more, 0.3 g / 10 min or more, 0.35 g / 10 min or more, or 0.4 g / 10 min or more.

[0045] The MFR of the microporous layer (B) is preferably lower than that of the microporous layer (A). By making the MFR of the microporous layer (B) lower than that of the microporous layer (A), the pore size of the microporous layer (A) of the obtained separator can be controlled to be larger than that of the microporous layer (B). Here, the ratio of the MFR of the microporous layer (B) to that of the microporous layer (A) is preferably 0.95 or less, more preferably 0.90 or less, and even more preferably 0.85 or less. The lower limit that can be combined with these upper limits is preferably 0.2 or more, more preferably 0.3 or more, and even more preferably 0.4 or more, from the viewpoint of membrane formation stability.

[0046] <Pentad fraction of microporous layer (B)> The lower limit of the pentad fraction of the polypropylene of the microporous layer (B) is preferably 94.0% or more, for example, 95.0% or more, 96.0% or more, 96.5% or more, 97.0% or more, 97.5% or more, 98.0% or more, 98.5% or more, or 99.0% or more, from the viewpoint of obtaining a microporous layer with low air permeability. The upper limit of the pentad fraction of the polypropylene that can be combined with these lower limits is not limited, but may be 99.9% or less, 99.8% or less, or 99.5% or less. The pentad fraction of the polypropylene is 13 Measured by C-NMR (nuclear magnetic resonance).

[0047] A pentad fraction of 94.0% or more of polypropylene indicates high crystallinity of the polypropylene. In separators obtained by the stretching perforation method, particularly the dry method, the amorphous parts between the crystalline parts are stretched to form pores, so if the polypropylene has high crystallinity, the pores become good and the air permeability can be kept low, which enables the battery to have high output.

[0048] <Area-average long pore diameter of microporous layer (B)> The area average long pore diameter (hereinafter simply referred to as "area average long pore diameter") of the pores in the ND-MD cross section of the microporous layer (B) is smaller than the area average long pore diameter of the microporous layer (A). For details of the relationship with the area average long pore diameter of the microporous layer (A), please refer to the section "Area average long pore diameter of the microporous layer (A)".

[0049] The area average long pore diameter of the microporous layer (B) is preferably 40 nm to 500 nm, more preferably 60 nm to 450 nm, even more preferably 80 nm to 400 nm, and still more preferably 100 nm to 350 nm. When the area average long pore diameter of the microporous layer (B) is within this range, clogging of the separator can be more effectively reduced and short circuits can be suppressed.

[0050] <Porosity of microporous layer (B)> The porosity of the microporous layer (B) is preferably 20% or more from the viewpoint of avoiding clogging in the power storage device and obtaining good air permeability of the separator, and is preferably 70% or less from the viewpoint of maintaining the strength of the separator. The porosity of the microporous layer (B) is more preferably 25% or more and 65% or less, further preferably 30% or more and 60% or less, and particularly preferably 35% or more and 55% or less.

[0051] <Thickness of microporous layer (B)> The thickness of the microporous layer (B) according to the present disclosure may be preferably 10 μm or less, for example, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4.5 μm or less, or 4 μm or less, from the viewpoint of increasing the energy density of the electricity storage device, etc. The lower limit of the thickness of the microporous layer (B) which can be combined with these upper limits may be preferably 1 μm or more, for example, 2 μm or more, 3 μm or more, or 3.5 μm or more, from the viewpoint of strength, etc.

[0052] Additives for the microporous layer (B) The microporous layer (B) containing 70% by mass or more of polypropylene may further contain, in addition to polypropylene, additives such as elastomers, crystal nucleating agents, antioxidants, fillers, etc., as necessary. The amount of the additives is not particularly limited, but is, for example, 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more based on the total mass of the microporous layer (B), and the upper limit of the amount of the additives that can be combined with these lower limits may be 10% by mass or less, 7% by mass or less, or 5% by mass or less.

[0053] <Microporous layer (C)> The separator for an electric storage device of the present disclosure may further include a microporous layer (C) containing 50% by mass or more of polyolefin in addition to the microporous layer (A) and the microporous layer (B). In this case, the separator for an electric storage device may include only one microporous layer (C) or two or more layers. The microporous layer (C) preferably contains 50% by mass or more of polypropylene. This allows good battery performance to be maintained even after storage at high temperature (140°C). The lower limit of the polypropylene content in the microporous layer (C) may be preferably 55% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more from the viewpoints of the wettability, thinning, and shutdown characteristics of the separator. The upper limit of the polypropylene content in the microporous layer (C), which can be combined with these lower limits, is not limited, and may be, for example, 60% by mass or less, 70% by mass or less, 80% by mass or less, 90% by mass or less, 95% by mass or less, 98% by mass or less, or 99% by mass or less, or may be 100% by mass.

[0054] <Material for the microporous layer (C)> The polypropylene of the microporous layer (C) may be the same material as the polypropylene of the microporous layer (A) and the microporous layer (B), or may be a polypropylene having a different chemical structure, more specifically, a polypropylene differing in at least one of the monomer composition, stereoregularity, molecular weight, and crystal structure.

[0055] The stereoregularity of the polypropylene of the microporous layer (C) is not limited, but may be, for example, atactic, isotactic, or syndiotactic homopolymer, etc. The polypropylene according to the present disclosure is preferably an isotactic or syndiotactic highly crystalline homopolymer.

[0056] The polypropylene of the microporous layer (C) is preferably a homopolymer, and may be a copolymer, such as a block polymer, in which a small amount of comonomer other than propylene, such as an α-olefin comonomer, is copolymerized. The amount of propylene structure contained as a repeating unit in the polypropylene is not limited, but may be, for example, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 99 mol% or more. The upper limit of the amount of the repeating unit of the comonomer is not limited, but may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less. The polypropylene may be used alone or in a mixture of two or more kinds.

[0057] The weight average molecular weight (Mw) of the polypropylene of the microporous layer (C) is preferably 300,000 or more from the viewpoint of the strength of the microporous layer, etc., and is preferably 1,500,000 or less from the viewpoint of increasing the pore size of the microporous layer and avoiding clogging. The Mw of the polypropylene is more preferably 500,000 or more and 1,300,000 or less, even more preferably 600,000 or more and 1,100,000 or less, still more preferably 700,000 or more and 1,050,000 or less, and particularly preferably 800,000 or more and 1,000,000 or less.

[0058] The upper limit of the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) of the polypropylene of the microporous layer (C) by the number average molecular weight (Mn) is preferably 20 or less, more preferably 15 or less, and the lower limit that can be combined with these upper limits may be preferably 4 or more, for example 4.5 or more, 5.0 or more, or 5.5 or more. The larger the Mw / Mn value of the polypropylene, the higher the melt tension of the resulting microporous layer tends to be. Therefore, it is preferable that the Mw / Mn value of the polypropylene is 4 or more, since the melt tension of the microporous layer (C) can be controlled to be larger than that of the microporous layer (B), and as a result, the pore size of the microporous layer (C) can be controlled to be smaller than that of the microporous layer (B). The weight average molecular weight, number average molecular weight, and Mw / Mn of the polyolefin of the present disclosure are polystyrene-equivalent molecular weights obtained by GPC (gel permeation chromatography) measurement.

[0059] The density of the polypropylene of the microporous layer (C) is preferably 0.85 g / cm 3 For example, 0.88 g / cm 3 More than 0.89g / cm 3 or more than 0.90g / cm 3 The upper limit of the density of the polypropylene, which can be combined with these lower limits, is preferably 1.1 g / cm 3 For example, 1.0 g / cm 3 Below, 0.98g / cm 3 Below, 0.97g / cm 3 Below, 0.96g / cm 3 Below, 0.95g / cm 3 Below, 0.94g / cm 3 Below, 0.93g / cm 3 or less than 0.92 g / cm 3 The density of polyolefins is related to the crystallinity of polypropylene, and the density of polypropylene can be less than 0.85 g / cm 3 By setting the above amount, the productivity of the microporous layer is improved, which is particularly advantageous in the dry method.

[0060] The microporous layer (C) may contain other resins in addition to polypropylene. Examples of other resins include polyolefins other than polypropylene (also referred to as "other polyolefins"). Polyolefins are polymers containing a monomer having a carbon-carbon double bond as a repeating unit. Monomers constituting polyolefins other than polypropylene are not limited, but include monomers having 2 or 4 to 10 carbon atoms and having a carbon-carbon double bond, such as ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Polyolefins are, for example, homopolymers, copolymers, or multi-stage polymers, and are preferably homopolymers. Specifically, polyethylene is preferred as the polyolefin from the viewpoint of shutdown characteristics and the like.

[0061] <Melt flow rate (MFR) of microporous layer (C)> The upper limit of the melt flow rate (MFR) of the microporous layer (C) (MFR of a single layer) is preferably 1.5 g / 10 min or less from the viewpoint of obtaining a microporous layer (C) with higher strength, and may be, for example, 1.4 g / 10 min or less, 1.3 g / 10 min or less, 1.2 g / 10 min or less, or 1.1 g / 10 min or less. The lower limit of the MFR of the microporous layer (C) (MFR of a single layer) that can be combined with these upper limits is not limited from the viewpoint of the moldability of the microporous layer (C), and may be, for example, 0.2 g / 10 min or more, 0.25 g / 10 min or more, 0.3 g / 10 min or more, 0.35 g / 10 min or more, or 0.4 g / 10 min or more. The MFR of the microporous layer (C) is measured under conditions of a load of 2.16 kg and a temperature of 230°C.

[0062] The MFR of the microporous layer (C) being 1.5 g / 10 min or less means that the molecular weight of the polyolefin contained in the microporous layer (C) is relatively high. A high molecular weight polyolefin tends to produce a high-strength microporous layer (C) because there are more tie molecules that bond crystalline substances together. A MFR of the microporous layer (C) being 0.2 g / 10 min or more ensures that the melt tension of the microporous layer (C) is not too low, making it easier to produce a high-strength, thin-film microporous layer.

[0063] From the viewpoint of obtaining a high-strength microporous layer (C), the MFR of the polypropylene constituting the microporous layer (C) is preferably 0.2 to 1.5 g / 10 min when measured under conditions of a load of 2.16 kg and a temperature of 230° C. The upper limit of the MFR of the polypropylene may be, for example, 1.4 g / 10 min or less, 1.3 g / 10 min or less, 1.2 g / 10 min or less, or 1.1 g / 10 min or less, from the viewpoint of obtaining a microporous layer with higher strength. The lower limit of the MFR of the polypropylene that can be combined with these upper limits is not limited, but may be, for example, 0.25 g / 10 min or more, 0.3 g / 10 min or more, 0.35 g / 10 min or more, or 0.4 g / 10 min or more, from the viewpoint of moldability of the microporous layer (C), etc.

[0064] <Pentad fraction of microporous layer (C)> The lower limit of the pentad fraction of the polypropylene in the microporous layer (C) is preferably 94.0% or more, for example, 95.0% or more, 96.0% or more, 96.5% or more, 97.0% or more, 97.5% or more, 98.0% or more, 98.5% or more, or 99.0% or more, from the viewpoint of obtaining a microporous layer with low air permeability. The upper limit of the pentad fraction of the polypropylene that can be combined with these lower limits is not limited, but may be 99.9% or less, 99.8% or less, or 99.5% or less. The pentad fraction of the polypropylene is 13 Measured by C-NMR (nuclear magnetic resonance).

[0065] A pentad fraction of 94.0% or more of polypropylene indicates high crystallinity of the polypropylene. In separators obtained by the stretching perforation method, particularly the dry method, the amorphous parts between the crystalline parts are stretched to form pores, so if the polypropylene has high crystallinity, the pores become good and the air permeability can be kept low, which enables the battery to have high output.

[0066] <Area-average long pore diameter of the microporous layer (C)> The area average long pore diameter (hereinafter also simply referred to as "area average long pore diameter") of the pores in the microporous layer (C) in the ND-MD cross section is preferably smaller than the area average long pore diameter of the microporous layer (B). Specifically, the area average long pore diameter of the microporous layer (C) is preferably 0.20 to 0.90 times, more preferably 0.50 to 0.90 times, of the area average long pore diameter of the microporous layer (B). This makes it possible to more effectively reduce clogging of the separator and suppress short circuits. When there are two or more microporous layers (C) and / or microporous layers (B), the area average long pore diameters of the microporous layer (C) and the microporous layer (B) are compared based on the average area average long pore diameter value of each layer.

[0067] The area average long pore diameter of the microporous layer (C) is preferably 20 nm to 450 nm, more preferably 40 nm to 400 nm, even more preferably 60 nm to 350 nm, and still more preferably 80 nm to 300 nm. When the area average long pore diameter of the microporous layer (C) is within this range, clogging of the separator can be more effectively reduced and short circuits can be suppressed.

[0068] <Porosity of the microporous layer (C)> The porosity of the microporous layer (C) is preferably 20% or more from the viewpoint of avoiding clogging in the electricity storage device and obtaining good air permeability of the separator, and is preferably 70% or less from the viewpoint of maintaining the strength of the separator. The porosity of the microporous layer (C) is more preferably 25% or more and 65% or less, further preferably 30% or more and 60% or less, and particularly preferably 35% or more and 55% or less.

[0069] <Thickness of microporous layer (C)> The thickness of the microporous layer (C) according to the present disclosure may be preferably 10 μm or less, for example, 8 μm or less, 7 μm or less, 6 μm or less, 5 μm or less, 4.5 μm or less, or 4 μm or less, from the viewpoint of increasing the energy density of the electricity storage device, etc. The lower limit of the thickness of the microporous layer (C) which can be combined with these upper limits may be preferably 1 μm or more, for example, 2 μm or more, 3 μm or more, or 3.5 μm or more, from the viewpoint of strength, etc.

[0070] Additives for the microporous layer (C) In addition to polypropylene, the microporous layer (C) may further contain additives such as elastomers, crystal nucleating agents, antioxidants, fillers, etc., as necessary. The amount of the additives is not particularly limited, but is, for example, 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more based on the total mass of the microporous layer (C), and the upper limit of the amount of the additives that can be combined with these lower limits may be 10% by mass or less, 7% by mass or less, or 5% by mass or less.

[0071] <Area average long pore diameter on the surface of the substrate> The substrate preferably contains polyolefin as a main component and has a first porous surface (X) and a second porous surface (Y) opposite to the first porous surface (X). The area average long pore diameter (S X ) is the area average long pore diameter (S Y ), preferably 1.05 to 10 times, more preferably 1.1 to 5 times, and even more preferably 1.2 to 3 times. Surface (X) and surface (Y) may be composed of a single (single layer) microporous layer, or surface (X) may be composed of one microporous layer among two or more laminated microporous layers, and surface (Y) may be composed of the other microporous layer among the laminated microporous layers. When the substrate has a laminated structure having at least one microporous layer (A) and at least one microporous layer (B), the surface on the microporous layer (A) side corresponds to the above-mentioned first porous surface (X), and the surface of the microporous membrane opposite to the microporous layer (A) corresponds to the second porous surface (Y).

[0072] The surface area average long pore diameter can be measured by image analysis of the obtained image by SEM observation of the surface of the separator. "Long pore diameter" means the pore diameter in MD. "MD" indicates the film formation direction of the microporous layer. For example, the MD of a separator having a microporous layer is the longitudinal direction if it is a roll. When measuring the average pore diameter from a surface SEM image, the number average pore diameter and the area average pore diameter can be calculated, but the number average pore diameter counts even very small pores as one pore, making it difficult to sufficiently correlate with the physical properties of the separator. Therefore, in order to better correlate with the physical properties of the separator, the area average pore diameter is used as the average pore diameter in this specification.

[0073] The area average long pore diameter (S X ) is the area average long pore diameter (S Y ) is 1.05 times or more, it means that the surface (X) has a larger pore diameter than the surface (Y). X ) is the area average long pore diameter (S Y ) or more, clogging of the substrate during battery evaluation (cycle testing) can be reduced, and short circuits due to the inclusion of foreign matter can be suppressed. X ) is the area average long pore diameter (S Y ) is believed to be sufficient to ensure the strength of the separator.

[0074] The area average long pore diameter (S X ) is preferably 80 nm or more and 600 nm or less, more preferably 120 nm or more and 550 nm or less, even more preferably 130 nm or more and 500 nm or less, and even more preferably 140 nm or more and 450 nm or less. When the area average long pore diameter of the surface (X) is 80 nm or more, clogging of the separator due to deposits in the electricity storage device can be more effectively reduced, and when it is 600 nm or less, the strength of the separator can be further improved. It is preferable to reduce clogging due to deposits in the electricity storage device, and for this purpose, it is preferable that the area average long pore diameter of the surface (X) is 80 nm or more.

[0075] The area average long pore diameter (S Y ) is preferably 20 nm or more and 500 nm or less, more preferably 30 nm or more and 450 nm or less, even more preferably 40 nm or more and 400 nm or less, and even more preferably 50 nm or more and 350 nm or less. When the area average long pore diameter of the surface (Y) is within this range, clogging of the separator can be more effectively reduced and short circuits can be suppressed.

[0076] <Layer structure of substrate> The substrate of the separator for an electricity storage device (also simply referred to as "substrate" in this specification) is composed of a single (single layer) microporous layer, or has at least one microporous layer (A) and one microporous layer (B). The substrate may have a multilayer structure of three or more layers having two or more microporous layers (A) and / or two or more microporous layers (B). Examples of the multilayer structure include a two-layer structure of microporous layer (A) / microporous layer (B) and a three-layer structure of microporous layer (A) / microporous layer (B) / microporous layer (A). The substrate may also have layers other than the microporous layer (A) and the microporous layer (B). Examples of the layers other than the microporous layer (A) and the microporous layer (B) include the above-mentioned microporous layer (C), a layer containing an inorganic substance, and a layer containing a heat-resistant resin. For example, the substrate may have a multilayer structure of four or more layers, such as microporous layer (A) / microporous layer (B) / microporous layer (C) / microporous layer (A). From the viewpoints of ease of production and suppression of curling of the separator, a symmetrical laminate structure is preferred.

[0077] When the substrate has a microporous layer (C), the substrate preferably has a three-layer structure of microporous layer (A) / microporous layer (B) / microporous layer (C). When the substrate has such a layered structure, clogging of the separator can be more effectively reduced and short circuits can be suppressed.

[0078] <Thickness of substrate> The upper limit of the thickness of the substrate is preferably 25 μm or less, and may be, for example, 22 μm or less, 20 μm or less, 18 μm or less, 16 μm or less, 14 μm or less, or 12 μm or less, from the viewpoint of increasing the energy density of the electricity storage device, etc. The lower limit of the thickness of the substrate, which can be combined with these upper limits, is preferably 6 μm or more, and may be, for example, 7 μm or more, 8 μm or more, 9 μm or more, or 10 μm or more, from the viewpoint of strength, etc.

[0079] <Air permeability of base material (air resistance)> The upper limit of the air permeability of the substrate is preferably 290 sec / 100 cm when the thickness of the substrate is converted to 16 μm. 3 For example, 280 seconds / 100 cm 3 Below, 270 seconds / 100cm 3 Below, 260 seconds / 100cm 3 or less than 250 seconds / 100 cm 3 The lower limit of the air permeability of the substrate that can be combined with these upper limits is not limited, but may be, for example, 50 seconds / 100 cm when converted into a substrate having a thickness of 16 μm. 3 Over 60 seconds / 100cm 3 or more, or 70 seconds / 100 cm 3 It may be more than that.

[0080] <Air permeability (air resistance) of the base material after high-temperature treatment> The substrate of the present disclosure preferably has an air permeability change rate of 100% or less after heating at 140° C. for 30 minutes in the atmosphere with the ends restrained (hereinafter also simply referred to as "after high-temperature treatment"). The air permeability change rate is calculated by the following formula: Air permeability change rate (%) = {air permeability after heating (sec / 100 cm 3 )-Air permeability before heating (sec / 100cm 3 )}÷Air permeability before heating (sec / 100cm 3 ) x 100 Note that the "state in which the ends are restrained" means that the heat treatment is performed in a state in which the ends of the substrate are fixed, assuming that the separator is fixed during the production of the electricity storage device.

[0081] In the case of a conventional separator having a substrate with a layer mainly composed of polyethylene, the air permeability after high-temperature treatment is 5000 sec / 100 cm 3 In contrast, an air permeability change rate of 100% or less means that the change in air permeability is very small even after exposure to high temperatures such as drying treatment. When the air permeability change rate is 100% or less, it is possible to ensure good battery performance after high-temperature drying during the manufacture of an electricity storage device. The air permeability change rate is preferably 80% or less, 60% or less, 40% or less, 20% or less, 10% or less, or 5% or less, and the lower limit that can be combined with these upper limits is not limited, but is preferably -5% or more, -3% or more, -2% or more, -1% or more, 0% or more, or more than 0%.

[0082] The upper limit of the air permeability of the substrate of the present disclosure after high temperature treatment is preferably 580 sec / 100 cm when converted into a substrate having a thickness of 16 μm. 3 For example, 500 seconds / 100 cm 3 Below, 450 seconds / 100cm 3 Below, 400 seconds / 100cm 3 or less than 350 seconds / 100 cm 3 The lower limit of the air permeability of the substrate after high-temperature treatment, which can be combined with these upper limits, is not limited, but may be, for example, 50 sec / 100 cm when the thickness of the substrate is converted to 16 μm. 3 Over 60 seconds / 100cm 3 or more, or 70 seconds / 100 cm 3 It may be more than that.

[0083] <Porosity of the substrate> The porosity of the substrate is preferably 20% or more from the viewpoint of avoiding clogging in the electricity storage device and obtaining good air permeability of the separator, and is preferably 70% or less from the viewpoint of maintaining the strength of the separator. The porosity of the substrate is more preferably 25% or more and 65% or less, further preferably 30% or more and 60% or less, and particularly preferably 35% or more and 55% or less.

[0084] <Puncture strength of base material> The lower limit of the puncture strength of the substrate, when converted to a thickness of 16 μm, is preferably 230 gf or more, 240 gf or more, 250 gf or more, 260 gf or more, 280 gf or more, 300 gf or more, or 320 gf or more. The upper limit of the puncture strength of the substrate, which can be combined with these lower limits, is not limited, but may be preferably 550 gf or less, for example 500 gf or less, or 480 gf or less, when converted to a thickness of 16 μm.

[0085] <Thermal shrinkage rate of the base material> The substrate preferably has a thermal shrinkage rate in the width direction (TD) of -1.0% or more and 3.0% or less after heat treatment at 150°C for 1 hour. That is, it means that the substrate has very small thermal shrinkage in the width direction even at high temperatures. When the thermal shrinkage rate is 3.0% or less, short circuit at high temperatures can be effectively suppressed. The reason why the thermal shrinkage rate is -1.0% or more is that when the thermal shrinkage rate is measured, the substrate may expand slightly in the width direction, and the thermal shrinkage rate may become a negative value less than 0%. The thermal shrinkage rate may be 0% or more or more than 0%. As a method for producing a substrate having a thermal shrinkage rate of -1.0% or more and 3.0% or less, for example, a method of producing the substrate by a uniaxially stretched dry method can be mentioned. In a wet separator, the thermal shrinkage in the width direction is generally very large, whereas in a uniaxially stretched dry separator, a substrate having a thermal shrinkage rate of -1.0% or more and 3.0% or less can be easily obtained.

[0086] <<Method for producing separator for power storage device>> The method for producing a separator for an electricity storage device includes a melt extrusion step of melt extruding a resin composition mainly composed of polypropylene (hereinafter also referred to as a "polypropylene-based resin composition") to obtain a resin film, and a pore forming step of opening holes in the obtained resin film to make it porous. The method for producing a microporous layer is broadly divided into a dry method in which no solvent is used in the pore forming step, and a wet method in which a solvent is used.

[0087] Examples of the dry method include a method in which a polypropylene-based resin composition is melt-kneaded and extruded, and then the polypropylene crystal interface is peeled off by heat treatment and stretching; and a method in which a polypropylene-based resin composition and an inorganic filler are melt-kneaded and formed into a film, and then the interface between the polypropylene and the inorganic filler is peeled off by stretching.

[0088] Examples of the wet method include a method in which a polypropylene resin composition and a pore-forming material are melt-kneaded to form a film, which is then stretched as necessary, and the pore-forming material is extracted; and a method in which the polypropylene resin composition is dissolved, and then the film is immersed in a poor solvent for polypropylene to solidify the polypropylene and simultaneously remove the solvent.

[0089] For melt-kneading of the polypropylene-based resin composition, a single screw extruder or a twin screw extruder can be used. In addition to these, for example, a kneader, a Labo Plastomill, a kneading roll, a Banbury mixer, etc. can also be used.

[0090] The polypropylene resin composition may contain, as desired, a resin other than polypropylene, an additive, etc., depending on the method for producing the microporous layer or the physical properties of the intended microporous layer. Examples of the additives include a pore-forming material, a fluorine-based flow modifier, a wax, a crystal nucleating material, an antioxidant, a metal soap such as an aliphatic carboxylic acid metal salt, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment. Examples of the pore-forming material include a plasticizer, an inorganic filler, or a combination thereof.

[0091] Examples of the plasticizer include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol.

[0092] Examples of inorganic fillers include oxide ceramics such as alumina, silica (silicon oxide), titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers.

[0093] The substrate is preferably produced by a dry lamellar crystal opening process in which the polypropylene crystal interface is peeled off by heat treatment and stretching. Here, the substrate having the microporous layer (A) and the microporous layer (B) is preferably produced by at least one of the following methods (i) and (ii): (i) a method for producing a substrate by coextrusion, comprising coextrusion forming a microporous layer (A) and a microporous layer (B), followed by annealing, cold stretching, hot stretching and heat relaxation; and (ii) A method for producing a substrate by lamination, in which the microporous layer (A) and the microporous layer (B) are separately extruded and laminated together, followed by annealing, cold stretching, hot stretching and heat relaxation.

[0094] Similarly, when the microporous layer (C) is further provided, the following method can be mentioned: (i) a method for producing a substrate by coextrusion, comprising coextrusion-forming a microporous layer (A), a microporous layer (B) and a microporous layer (C), and subjecting the coextrusion-formed substrate to annealing, cold stretching, hot stretching and heat relaxation steps; (ii) A method for producing a substrate by lamination, comprising extruding at least one of the microporous layer (A), the microporous layer (B), and the microporous layer (C) separately, bonding them together by lamination, and then subjecting them to annealing, cold stretching, hot stretching, and heat relaxation steps.

[0095] The absolute value and ratio of the area average long pore diameter in the ND-MD cross section of the microporous layer (A) and the microporous layer (B), and optionally the microporous layer (C), can be adjusted to the preferred range of the present disclosure by changing the molecular weight of the polypropylene of each layer and adding an additive. The present inventors have found that by using a polypropylene having a higher molecular weight than the other layers in one microporous layer, it is possible to control the pore diameter to be smaller than that of the other layers. In addition, the present inventors have found that by adding an additive of a specific structure, such as a styrene-olefin copolymer, to the microporous layer, it is possible to control the pore diameter to be larger than that of the other layers. Furthermore, the present inventors have found that by strictly controlling the pore diameter of each layer, it is possible to achieve both battery performance, heat resistance, and short circuit suppression.

[0096] When the substrate has a laminated structure of two or more layers, the area average long pore diameter (S X ) and the area-average long pore diameter (S Y ) to the preferred range of the present disclosure, the absolute value and ratio can be adjusted by changing the molecular weight of the polypropylene of each surface layer and adding an additive. By using a polypropylene having a higher molecular weight than the other layers for the microporous layer having one surface, the pore size can be controlled to be smaller than that of the other layers. In addition, by adding an additive having a specific structure, such as a styrene-olefin copolymer, to the microporous layer, the pore size can be controlled to be larger than that of the other layers. Furthermore, the present inventors have found that by strictly controlling the pore size of each layer, it is possible to achieve both battery performance, heat resistance, and short circuit suppression.

[0097] When the substrate is made of a single (single) microporous layer, the area-average pore diameter (S X ) and the area-average long pore diameter (S Y The absolute value and ratio of the stoichiometric ratio (Sr) can be adjusted to the preferred range of the present disclosure by applying a molecular weight gradient within a single layer during film formation and by incorporating more additive on one side. The pore size of the surface on the side with a lower molecular weight and the side with more additive can be controlled to be larger.

[0098] Multilayer separators consisting of a layer with a small pore size mainly made of polypropylene and a layer with a large pore size containing polyethylene have been known for some time. Although not limited by theory, by using polyethylene having high crystallinity and a crystal size larger than that of polypropylene, the pore size of the polyethylene-containing layer can be controlled to be larger than that of the layer mainly made of polypropylene. However, when the substrate has a layer mainly made of polyethylene, there is a problem that the pores are blocked by high-temperature heat treatment at or above the melting point of polyethylene (128°C), and the separator no longer functions. On the other hand, in a multilayer structure consisting of a layer mainly made of polypropylene and not having a layer mainly made of polyethylene, it was very difficult to independently control the pore size of each layer and manufacture a multilayer structure in which the pore size of each layer is different.

[0099] Of the co-extrusion process (i) and the lamination process (ii), the co-extrusion process (i) is preferred from the viewpoint of production costs, etc. In the co-extrusion process (i), the extrusion film-forming conditions for the microporous layers (A) to (C) are preferably such that the resin is discharged at the lowest possible temperature and effectively quenched by blowing low-temperature air. After film formation, it is preferable to quench with air, and the temperature of the blown air is preferably 20°C or lower, more preferably 15°C or lower. By blowing cold air controlled at such a low temperature, the resin after film formation is quenched and uniformly oriented in the MD.

[0100] The method for producing the substrate may include an annealing step after extrusion film formation. By carrying out the annealing step, the crystal structure of the microporous layers (A) to (C) grows, and the pore opening tends to be improved. By carrying out the annealing step for a long time at a specific temperature, it tends to be possible to obtain a good area average long pore diameter for both the microporous layers (A) to (C). This is thought to be because the crystals grow without disturbing the crystal structure, and high pore opening is obtained. In addition, by carrying out the annealing step for a long time at a specific temperature, it tends to be possible to obtain a good area average long pore diameter for both the microporous layers (A) and (B). This is thought to be because the crystals grow without disturbing the crystal structure, and high pore opening is obtained. In the annealing step, it is preferable to carry out the annealing treatment at a temperature range of 115°C or more and 160°C or less, preferably for 20 minutes or more, more preferably for 60 minutes or more, from the viewpoint of obtaining a good area average long pore diameter and preventing clogging of the electricity storage device by obtaining a good area average long pore diameter.

[0101] The method for producing a substrate may include a stretching step after the annealing step, during the hole forming step, or before or after the hole forming step. As the stretching treatment, either uniaxial stretching or biaxial stretching can be used. Although not limited, uniaxial stretching is preferred from the viewpoint of production costs when using a dry method. Biaxial stretching is preferred from the viewpoint of improving the strength of the obtained substrate. Examples of biaxial stretching include simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and multiple stretching. Simultaneous biaxial stretching is preferred from the viewpoint of improving puncture strength, uniformity of stretching, and shutdown property. In addition, sequential biaxial stretching is preferred from the viewpoint of ease of control of plane orientation. When a sheet-like molded body is stretched in a biaxial direction at a high magnification, the molecules are oriented in the plane direction, so that a substrate that is difficult to tear and has high puncture strength tends to be obtained.

[0102] In order to suppress the thermal shrinkage of the substrate, a heat treatment step may be performed for the purpose of heat setting after the stretching step or the hole forming step. The heat treatment step may include a stretching operation performed in a predetermined temperature atmosphere and at a predetermined stretch ratio for the purpose of adjusting physical properties, and / or a relaxation operation performed in a predetermined temperature atmosphere and at a predetermined relaxation ratio for the purpose of reducing stretching stress. The relaxation operation may be performed after the stretching operation. These heat treatment steps may be performed using a tenter or roll stretching machine.

[0103] The resulting substrate can itself be used as a separator for an electrical storage device. Optionally, the substrate may be provided with a further layer of a coating layer on one or both sides.

[0104] <Electricity storage device> The power storage device of the present disclosure includes the power storage device separator of the present disclosure. The power storage device of the present disclosure has a positive electrode and a negative electrode, and the power storage device separator is preferably laminated between the positive electrode and the negative electrode. The microporous layer (A) constituting the outermost layer of the substrate is preferably disposed opposite the negative electrode side. Since clogging of the separator in the power storage device is mostly caused by deposits on the surface of the negative electrode, clogging of the separator can be effectively reduced by facing the microporous layer (A) having a relatively large pore size to the negative electrode side. The surface (X) of the substrate is preferably disposed opposite the negative electrode side. Since clogging of the separator in the power storage device is mostly caused by deposits on the surface of the negative electrode, clogging of the separator can be effectively reduced by facing the surface (X) having a relatively large pore size to the negative electrode side.

[0105] Examples of the power storage device include, but are not limited to, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel hydrogen batteries, nickel cadmium batteries, electric double layer capacitors, lithium ion capacitors, redox flow batteries, lithium sulfur batteries, lithium air batteries, and zinc air batteries. Among these, from the viewpoint of practicality, lithium secondary batteries, lithium ion secondary batteries, nickel hydrogen batteries, and lithium ion capacitors are preferred, and lithium ion secondary batteries are more preferred.

[0106] The electricity storage device can be produced, for example, by stacking a positive electrode and a negative electrode with the separator described above interposed therebetween and winding them as necessary to form a laminated electrode body or a wound electrode body, which is then loaded into an outer casing, connecting the positive and negative electrodes to the positive and negative electrode terminals of the outer casing via a lead body or the like, and further injecting a nonaqueous electrolyte solution containing a nonaqueous solvent such as a chain or cyclic carbonate and an electrolyte such as a lithium salt into the outer casing and then sealing the outer casing.

[0107] The power storage device is more preferably a lithium ion secondary battery. Preferred embodiments of the lithium ion secondary battery are described below, but the power storage device of the present disclosure is not limited to a lithium ion secondary battery.

[0108] The positive electrode is not particularly limited as long as it functions as a positive electrode of a lithium ion secondary battery, and a known positive electrode can be used. The positive electrode preferably contains at least one material selected from the group consisting of materials capable of absorbing and releasing lithium ions as a positive electrode active material. From the viewpoint of battery capacity and safety, the positive electrode active material is preferably a lithium cobalt oxide represented by LiCoO2, a spinel-type lithium manganese oxide represented by Li2Mn2O4, or a lithium manganese oxide represented by Li2Mn 1.5 Ni 0.5Examples of the lithium-containing composite metal oxide include a spinel-type lithium nickel manganese oxide represented by LiCoO4, a lithium nickel oxide represented by LiNiO2, a lithium-containing composite metal oxide represented by LiMO2 (M represents two or more elements selected from the group consisting of Ni, Mn, Co, AI, and Mg), and a lithium iron phosphate compound represented by LiFePO4. Among these, from the viewpoint of high safety and long-term stability, more preferred are a lithium cobalt oxide represented by LiCoO2, a lithium nickel oxide represented by LiNiO2, a lithium-containing composite metal oxide represented by LiMO2 (M represents two or more elements selected from the group consisting of Ni, Mn, Co, AI, and Mg), and a lithium iron phosphate compound represented by LiFePO4, and a lithium iron phosphate compound represented by LiFePO4 is particularly preferred.

[0109] The negative electrode is not particularly limited as long as it acts as the negative electrode of the lithium ion secondary battery, and may be a known one. The negative electrode preferably contains one or more materials selected from the group consisting of materials capable of absorbing and releasing lithium ions and metallic lithium as the negative electrode active material. That is, the negative electrode preferably contains one or more materials selected from the group consisting of metallic lithium, carbon materials, materials containing elements capable of forming an alloy with lithium, and lithium-containing compounds as the negative electrode active material. Examples of such materials include, in addition to metallic lithium, hard carbon, soft carbon, artificial graphite, natural graphite, graphite, pyrolytic carbon, coke, glassy carbon, baked bodies of organic polymer compounds, mesocarbon microbeads, carbon fibers, activated carbon, graphite, carbon colloids, and carbon black. EXAMPLES

[0110] Measurement and evaluation methods [Melt flow rate (MFR) measurement] The melt flow rate (MFR) of the microporous layer was measured at a temperature of 230°C and a load of 2.16 kg (unit: g / 10 min) in accordance with JIS K 7210. The MFR of polypropylene was measured at a temperature of 230°C and a load of 2.16 kg in accordance with JIS K 7210. However, the melt flow rate (MFR) of polyethylene and the melt flow rate (MFR) of the microporous layer containing 50% by mass or more of polyethylene were measured at a temperature of 190°C and a load of 2.16 kg in accordance with JIS K 7210.

[0111] [Measurement of Mw and Mn by GPC (gel permeation chromatography)] A calibration curve was created by measuring standard polystyrene under the following conditions using an Agilent PL-GPC220. Chromatography was also performed on the sample polymer under the same conditions, and the weight average molecular weight (Mw), number average molecular weight (Mn), and the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn) of the polymer in terms of polystyrene were calculated based on the calibration curve under the following conditions. Column: TSKgel GMHHR-H(20) HT (7.8mmI.D.×30 cm) x 2 Mobile phase: 1,2,4-trichlorobenzene Detector: RI Column temperature: 160℃ Sample concentration: 1mg / ml Calibration curve: Polystyrene

[0112] [Melt tension measurement] The melt tension (mN) of the microporous membrane was measured under the following conditions using a Capillograph manufactured by Toyo Seiki Seisakusho. Capillary: diameter 1.0mm, length 20mm Cylinder extrusion speed: 2mm / min Take-off speed: 60m / min ·Temperature: 230℃

[0113] [Measurement of pentad fraction] The pentad fraction of polypropylene was assigned based on the description in the Polymer Analysis Handbook (edited by the Japan Society for Analytical Chemistry). 13 The values ​​were calculated from the C-NMR spectrum by the peak height method. 13 The C-NMR spectrum was measured using a JEOL-ECZ500 by dissolving polypropylene pellets in o-dichlorobenzene-d at a measurement temperature of 145°C and 25,000 cumulative cycles.

[0114] [Measurement of thickness (μm)] The thickness (μm) of the substrate was measured using a Mitutoyo Digimatic Indicator IDC112 at room temperature of 23±2° C. The thickness of each microporous layer was calculated from cross-sectional SEM image data obtained by the evaluation method for the area average long pore diameter described below.

[0115] [Measurement of porosity (%)] A sample measuring 10 cm x 10 cm square was cut from the separator or microporous layer, and its volume (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) the porosity was calculated using the following equation. Porosity (%) = (volume-mass / density) / volume x 100

[0116] [Air permeability (sec / 100cm) 3 ) Measurement Using a Gurley air permeability tester conforming to JIS P-8117, the air permeability resistance (sec / 100cm 3 ) was measured, divided by the thickness, and then multiplied by 16 to calculate the air permeability converted into a 16 μm thickness.

[0117] [Air permeability after high temperature treatment (sec / 100cm 3 ) Measurement The substrate was cut into a square of 100 mm in both MD and TD, and the four edges of the square were fixed to a metal frame and placed in a hot air dryer (DF1032, manufactured by Yamato Scientific Co., Ltd.) and heat-treated at normal pressure in the atmosphere at 140°C for 30 minutes. After heat treatment, the sample was removed from the hot air dryer and allowed to cool at room temperature for 10 minutes. The substrate was then removed from the metal frame, and the air resistance (sec / 100 cm) of the substrate was measured using a Gurley air permeability meter conforming to JIS P-8117. 3 ) was measured, divided by the thickness, and then multiplied by 16 to calculate the air permeability after high-temperature treatment (converted into a thickness of 16 μm). The rate of change in air permeability was calculated using the following formula: Air permeability change rate (%) = {air permeability after heating (sec / 100 cm 3 )-Air permeability before heating (sec / 100cm 3 )}÷Air permeability before heating (sec / 100cm 3 ) x 100 It was calculated by:

[0118] [Measurement of TD heat shrinkage rate (%)] The substrate was cut into a square of 50 mm in MD / TD, and the obtained samples were placed in a hot air dryer (Yamato Scientific Co., Ltd., DF1032) and heat-treated at normal pressure in the air at 150°C for 1 hour. After heat treatment, the sample was removed from the hot air dryer and allowed to cool at room temperature for 10 minutes, after which the dimensional shrinkage rate was determined. The sample was placed on copy paper or the like so as not to adhere to the inner wall of the dryer or to fuse together. Heat shrinkage rate (%): (dimension before heating (mm) - dimension after heating (mm)) / (dimension before heating (mm)) x 100

[0119] [Measurement of area average long pore diameter] (1) Area average pore diameter in ND-MD cross section The area average long pore diameter in the ND-MD cross section was measured by image analysis in cross-sectional SEM observation. As a pretreatment, the separator was stained with ruthenium, and an ND-MD cross-sectional sample was prepared by freeze fracturing. The above cross-sectional sample was fixed to a SEM sample stage for cross-sectional observation with a conductive adhesive (carbon-based) and dried, and then osmium coating was performed as a conductive treatment using an osmium coater (HPC-30W, manufactured by Vacuum Device Co., Ltd.) under the conditions of an applied voltage adjustment knob setting of 4.5 and a discharge time of 0.5 seconds, to prepare a microscopic sample. Next, using a scanning electron microscope (Hitachi High-Technologies S-4800), any three points on the microporous membrane ND-MD cross section were observed under the conditions of an acceleration voltage of 1 kV, a detection signal of LA10, a working distance of 5 mm, and a magnification of 5000 times.

[0120] The observed images were binarized using the Otsu method with the image processing software ImageJ, the resin part and the pore part were separated, and the average long diameter of the pores was calculated. 2 The following holes were excluded from the measurement. The average diameter was calculated from the area of ​​each hole by the area average. Here, in order to avoid overestimating the contribution of extremely small holes, the average value was calculated by the area average, which is the weighted average of the area of ​​each hole, rather than the number average divided by the number of holes.

[0121] (2) Area average pore diameter on the surface of the substrate The area average long pore diameter on the surface of the substrate was measured by image analysis in surface SEM observation. When the surface of the substrate had an arbitrary coating layer, the coating layer was removed by immersing the substrate in acetone for 3 minutes as a pretreatment, and then peeling the coating layer by hand, and then washing with water and drying at room temperature overnight. The above sample was fixed to a SEM sample stage for surface observation with a conductive adhesive (carbon-based), dried, and then osmium coating was performed as a conductive treatment using an osmium coater (HPC-30W, manufactured by Vacuum Device Co., Ltd.) under the conditions of an applied voltage adjustment knob setting of 4.5 and a discharge time of 0.5 seconds, and used as a microscopic specimen. Next, a scanning electron microscope (Hitachi High-Technologies S-4800) was used to observe three arbitrary points on the surface of the microporous membrane under the conditions of an acceleration voltage of 1 kV, a detection signal of LA10, a working distance of 5 mm, and a magnification of 5000 times. From the obtained image, a range of 20 μm in the MD direction × 3 μm in the ND direction was observed as an observation image. The observed images were binarized using the Otsu method with the image processing software ImageJ, the resin part and the pore part were separated, and the average long diameter of the pores was calculated. 2 The following pores were excluded from the measurement: The average diameter was calculated by averaging the area of ​​each pore.

[0122] [Evaluation of cycle capacity retention and clogging] The electrolyte used was a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:2, containing 1 mol / L of LiPF6 as a lithium salt.

[0123] The positive electrode active material is lithium nickel manganese cobalt mixed oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), carbon black powder (manufactured by Timcal, product name: SuperP Li) as a conductive additive, and PVDF as a binder were mixed in a mass ratio of mixed oxide:conductive additive:binder=100:3.5:3. The mixture was applied to both sides of an aluminum foil serving as a positive electrode current collector with a thickness of 15 μm, dried, and then pressed with a roll press to prepare a double-sided coated positive electrode.

[0124] Graphite powder (manufactured by Hitachi Chemical Co., Ltd., product name: MAG) with a particle diameter of 22 μm (D50) as the negative electrode active material, a binder (manufactured by Zeon Corporation, product name: BM400B), and carboxymethyl cellulose (manufactured by Daicel Corporation, product name: #2200) as a thickener were mixed in a mass ratio of graphite powder:binder:thickener = 100:1.5:1.1 and applied to one side and both sides of copper foil as a negative electrode current collector with a thickness of 10 μm. The solvent was dried and removed, and then the coated copper foil was pressed with a roll press to produce a single-sided coated negative electrode and a double-sided coated negative electrode, respectively.

[0125] The obtained positive and negative electrodes were laminated in the order of single-sided coated negative electrode / double-sided coated positive electrode / double-sided coated negative electrode / double-sided coated positive electrode / single-sided coated negative electrode, with the separator prepared below sandwiched between the opposing surfaces of the active materials, and the MD end face of the separator was fixed by sealing. The microporous layer (A) was arranged to face the negative electrode. Next, the obtained laminate was inserted into a bag (battery exterior) made of a laminate film in which both sides of an aluminum foil (thickness 40 μm) were covered with a resin layer, with the positive and negative terminals protruding. After that, it was dried in the air at 80 ° C. for 12 hours, and then 0.8 mL of the electrolyte prepared as described above was injected into the bag, and the bag was vacuum sealed to prepare a sheet-shaped lithium ion secondary battery.

[0126] The obtained sheet-shaped lithium ion secondary battery was placed in a thermostatic chamber (manufactured by Futaba Scientific Co., Ltd., product name: PLM-73S) set at 25°C, connected to a charge / discharge device (manufactured by Asuka Electronics Co., Ltd., product name: ACD-01), and left to stand for 16 hours. The battery was then charged at a constant current of 0.05C, and after the voltage reached 4.35V, it was charged at a constant voltage of 4.35V for 2 hours, and then discharged at a constant current of 0.2C to 3.0V. This charge / discharge cycle was repeated three times to perform initial charging / discharging of the battery. Note that 1C refers to the current value when the entire capacity of the battery is discharged in 1 hour.

[0127] After the initial charge and discharge, the battery was placed in a thermostatic chamber set at 25°C, and the battery was charged at a constant current of 1C. After the voltage reached 4.35V, the battery was charged at a constant voltage of 4.35V for 1 hour, and then discharged at a constant current of 1C to 3.0V. This charge and discharge cycle was repeated 100 times to perform a cycle test on the battery.

[0128] The value (percentage) obtained by dividing the discharge capacity (mAh) at the 100th cycle by the discharge capacity (mAh) at the 1st cycle was taken as the cycle capacity retention rate. After the completion of 100 cycles, the sheet-shaped lithium ion secondary battery was disassembled under an argon atmosphere, the separator was taken out, and immersion washing was performed three times using ethyl methyl carbonate. The separator negative electrode side surface was observed under a microscope in a range of 1 mm square to confirm the presence or absence of clogging on the separator surface. If the pores on the separator surface were filled with deposits by 50% or more, it was judged as having clogging, and if the pores on the separator surface were not filled with deposits by 50% or more, it was judged as not having clogging. The above-mentioned clogging was confirmed at 10 places, and the percentage of the pores judged as having clogging was calculated.

[0129] [Short-circuit evaluation] Five sheets of lithium ion secondary batteries were prepared by the method described in the evaluation of cycle capacity retention rate. The obtained sheet lithium ion secondary batteries were placed in a thermostatic chamber (manufactured by Futaba Scientific Co., Ltd., product name: PLM-73S) set at 25°C, connected to a charge / discharge device (manufactured by Asuka Electronics Co., Ltd., product name: ACD-01), and left to stand for 16 hours. The battery was then charged at a constant current of 0.05C, and after the voltage reached 4.35V, it was charged at a constant voltage of 4.35V for 2 hours, and then discharged at a constant current of 0.2C to 3.0V. This charge / discharge cycle was repeated three times to perform initial charging / discharging of the battery. Note that 1C indicates the current value when the full capacity of the battery is discharged in 1 hour.

[0130] After the initial charge and discharge, the sheet-shaped lithium ion secondary battery was charged at a constant current of 0.5 C while being pressurized to 0.5 MPa at 25° C., and after the voltage reached 4.5 V, it was charged at a constant voltage of 4.5 V for 1 hour, and then left in an open circuit state for 1 hour. Here, batteries that did not reach 4.5 V even after 1 hour of constant current charging and batteries whose voltage dropped to 4.3 V or less during the 1 hour of open circuit state were judged to have a short circuit, and the percentage of batteries judged to have a short circuit was calculated.

[0131] [High temperature and dryness resistance evaluation] The electrolyte used was a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:2, containing 1 mol / L of LiPF6 as a lithium salt.

[0132] The positive electrode active material is lithium nickel manganese cobalt mixed oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2), carbon black powder (manufactured by Timcal, product name: SuperP Li) as a conductive additive, and PVDF as a binder were mixed in a mass ratio of mixed oxide:conductive additive:binder=100:3.5:3. The mixture was applied to both sides of an aluminum foil serving as a positive electrode current collector with a thickness of 15 μm, dried, and then pressed with a roll press to prepare a double-sided coated positive electrode.

[0133] Graphite powder (manufactured by Hitachi Chemical Co., Ltd., product name: MAG) with a particle diameter of 22 μm (D50) as the negative electrode active material, a binder (manufactured by Zeon Corporation, product name: BM400B), and carboxymethyl cellulose (manufactured by Daicel Corporation, product name: #2200) as a thickener were mixed in a mass ratio of graphite powder:binder:thickener = 100:1.5:1.1 and applied to one side and both sides of copper foil as a negative electrode current collector with a thickness of 10 μm. The solvent was dried and removed, and then the coated copper foil was pressed with a roll press to produce a single-sided coated negative electrode and a double-sided coated negative electrode, respectively.

[0134] The obtained positive and negative electrodes were laminated in the order of single-sided coated negative electrode / double-sided coated positive electrode / double-sided coated negative electrode / double-sided coated positive electrode / single-sided coated negative electrode, with the separator prepared below sandwiched between the opposing surfaces of the active materials, and the MD end face of the separator was fixed by sealing. The microporous layer (A) was arranged to face the negative electrode. Next, the obtained laminate was inserted into a bag (battery exterior) made of a laminate film in which both sides of an aluminum foil (thickness 40 μm) were covered with a resin layer, with the positive and negative terminals protruding. After that, it was dried in the air at 140 ° C. for 30 minutes, and then 0.8 mL of the electrolyte prepared as described above was poured into the bag, and the bag was vacuum sealed to produce a sheet-shaped lithium ion secondary battery that had been subjected to high-temperature drying treatment. The obtained sheet-shaped lithium ion secondary battery was placed in a thermostatic chamber (manufactured by Futaba Scientific Co., Ltd., product name: PLM-73S) set at 25°C, connected to a charger / discharger (manufactured by Asuka Electronics Co., Ltd., product name: ACD-01), and left to stand for 16 hours. The battery was then charged at a constant current of 0.5C to check whether it could be charged. A normal secondary battery reaches the target voltage of 4.35V within 3 hours, but a battery that has lost ion conductivity sees a sudden rise in voltage to 5V or higher within a few minutes, triggering an emergency stop. A battery that triggered the emergency stop was determined to be unchargeable.

[0135] Example 1 [Preparation of microporous layer] As the resin for the microporous layer (A), a high molecular weight polypropylene resin ("PP1" in Table 1, MFR (230°C) = 1.0 g / 10 min, density = 0.91 g / cm 3 A resin material was obtained by dry blending 95% by mass of ethylene-butene random copolymer elastomer ("C2C4" in Table 1) and 5% by mass of ethylene-butene random copolymer elastomer. The obtained resin material was melted in a 2.5-inch extruder and fed to both outer layers of a two-kind, three-layer co-extrusion T-die using a gear pump. In addition, a high molecular weight polypropylene resin ("PP1" in Table 1, MFR (230°C) = 1.0 g / 10 min, density = 0.91 g / cm) was used as the resin for the microporous layer (B). 3) was melted in a 2.5-inch extruder and fed to the inner layer of the two-kind, three-layer co-extrusion T-die using a gear pump. The temperature of the T-die was set to 220°C, and after the molten polymer was discharged from the T-die, the discharged resin was cooled by blowing in air while being wound up on a roll to obtain a precursor sheet with an A / B / A layer structure of approximately 17 μm in thickness. Here, the TD lip width of the T-die was set to 500 mm, the distance between the lips of the T-die (lip clearance) was set to 2.4 mm, and discharge was performed at a discharge rate of 6 kg / h.

[0136] The obtained precursor was then placed in a dryer and annealed for 20 minutes at 120° C. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125° C. without shrinking and hot stretched to 140%, and then relaxed by 15%, to obtain a substrate having a three-layer structure consisting of A / B / A layers.

[0137] Examples 2 to 4, Examples 7 to 16, Comparative Examples 1 to 8 Microporous membranes were obtained in the same manner as in Example 1, except that the raw materials and stretching conditions were changed as shown in Tables 1 to 3, and the resulting separators were evaluated. In Tables 1 to 3, "PP1," "PP2," "PP3," "PP4," and "PP5" are polypropylene resins shown in Table 4. In Tables 1 to 3, "SEPS" refers to a styrene-ethylene propylene-styrene block copolymer. In Tables 1 to 3, "PE" refers to polyethylene (MFR (190°C) = 0.4g / 10min).

[0138] Example 5 Instead of the two-kind, three-layer co-extrusion T-die, a two-kind, two-layer co-extrusion T-die was installed, and film formation was performed under the same conditions as in Example 1 using the raw materials shown in Table 1, to obtain a precursor sheet with an A / B layer structure approximately 17 μm thick.

[0139] The obtained precursor was then placed in a dryer and annealed for 20 minutes at 120° C. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125° C. without shrinking and hot stretched to 140%, and then relaxed by 15%, to obtain a substrate having a two-layer structure consisting of A / B layers.

[0140] Example 6 Instead of the two-kind, three-layer co-extrusion T-die, a three-kind, three-layer co-extrusion T-die was installed, and film formation was performed under the same conditions as in Example 1 using the raw materials shown in Table 1, to obtain a precursor sheet with an A / B / C layer structure approximately 17 μm thick.

[0141] The obtained precursor was then placed in a dryer and annealed for 20 minutes at 120° C. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125° C. without shrinking and hot stretched to 140%, and then relaxed by 15%, to obtain a substrate having a three-layer structure consisting of A / B / C layers.

[0142] Example 17 The electrolyte used was a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:2, containing 1 mol / L of LiPF6 as a lithium salt.

[0143] A lithium iron phosphate compound represented by LiFePO4 as a positive electrode active material, carbon black powder (manufactured by Timcal, product name: SuperP Li) as a conductive additive, and PVDF as a binder were mixed in a mass ratio of mixed oxide:conductive additive:binder = 92:5:3. This mixture was applied to both sides of an aluminum foil as a positive electrode current collector with a thickness of 15 μm, dried, and pressed with a roll press to prepare a double-sided coated positive electrode.

[0144] Graphite powder (Hitachi Chemical Co., Ltd., product name: MAG) with a particle diameter of 22 μm (D50) as the negative electrode active material, binder (Zeon Corporation, product name: BM400B), and carboxymethyl cellulose (Daicel Corporation, product name: #2200) as a thickener were mixed in a mass ratio of graphite powder: binder: thickener = 100: 1.5: 1.1. This mixture was applied to one side and both sides of a copper foil as a negative electrode current collector with a thickness of 10 μm, the solvent was dried and removed, and then the applied copper foil was pressed with a roll press to prepare a single-sided coated negative electrode and a double-sided coated negative electrode, respectively.

[0145] The obtained positive and negative electrodes were laminated in the order of single-sided coated negative electrode / double-sided coated positive electrode / double-sided coated negative electrode / double-sided coated positive electrode / single-sided coated negative electrode, with the separator prepared in Example 10 sandwiched between the opposing surfaces of the active materials, and the MD end face of the separator was fixed by sealing. The microporous layer (A) was arranged to face the negative electrode. Next, the obtained laminate was inserted into a bag (battery exterior) made of a laminate film in which both sides of an aluminum foil (thickness 40 μm) were covered with a resin layer, with the terminals of the positive and negative electrodes protruding. After that, it was dried in the air at 80 ° C. for 12 hours, and then 0.8 mL of the electrolyte prepared as described above was poured into the bag, and the bag was vacuum sealed to prepare a sheet-shaped lithium ion secondary battery having a lithium iron phosphate compound as the positive electrode.

[0146] The sheet-shaped lithium ion secondary battery having the obtained lithium iron phosphate compound in the positive electrode was placed in a thermostatic chamber (manufactured by Futaba Scientific Co., Ltd., product name: PLM-73S) set at 25°C, connected to a charge / discharge device (manufactured by Asuka Electronics Co., Ltd., product name: ACD-01), and left to stand for 16 hours. The battery was then charged at a constant current of 0.05C, and after the voltage reached 3.65V, it was charged at a constant voltage of 3.65V for 2 hours, and then discharged at a constant current of 0.2C to 2.40V. This charge / discharge cycle was repeated three times to perform initial charging / discharging of the battery. Note that 1C refers to the current value when the full capacity of the battery is discharged in 1 hour.

[0147] After the initial charge and discharge, the battery was placed in a thermostatic chamber set at 25° C. The battery was charged at a constant current of 1 C, and after the voltage reached 3.65 V, it was charged at a constant voltage of 3.65 V for 1 hour, and then discharged at a constant current of 1 C to 2.40 V. This charge and discharge cycle was repeated 10 times. It was confirmed that the obtained battery could be charged and discharged well.

[0148] [Table 1]

[0149] [Table 2]

[0150] [Table 3]

[0151] [Table 4]

[0152] Example 18 [Preparation of microporous layer] As the resin for the microporous layer (A), a high molecular weight polypropylene resin ("PP1" in Table 5, MFR (230°C) = 1.0 g / 10 min, density = 0.91 g / cm 3 A resin material was obtained by dry blending 95% by weight of styrene-ethylene propylene-styrene block copolymer ("SEPS" in Table 5) and 5% by weight of styrene-ethylene propylene-styrene block copolymer ("SEPS" in Table 5). The obtained resin material was melted in a 2.5-inch extruder and fed to one of the outer layers of a two-kind, two-layer co-extrusion T-die using a gear pump. In addition, a high molecular weight polypropylene resin ("PP2" in Table 5, MFR (230°C) = 0.5 g / 10 min, density = 0.91 g / cm3) was used as the resin for the microporous layer (B). 3) was melted in a 2.5-inch extruder and fed to the other outer layer of the two-kind, two-layer co-extrusion T-die using a gear pump. The temperature of the T-die was set to 220°C, and after the molten polymer was discharged from the T-die, the discharged resin was cooled by blowing in air while being wound up on a roll to obtain a precursor sheet with an A / B layer structure of approximately 17 μm in thickness. Here, the lip width of the T-die in the TD direction was set to 500 mm, the distance between the lips of the T-die (lip clearance) was set to 2.4 mm, and discharge was performed at a discharge rate of 6 kg / h.

[0153] The obtained precursor was then placed in a dryer and annealed at 120°C for 20 minutes. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125°C without shrinking, and hot stretched to 140%, and then relaxed by 15%, to obtain a separator substrate having a two-layer structure consisting of A / B. Here, the surface on the microporous layer (A) side has a large pore size (surface (X)), and the surface on the microporous layer (B) side has a small pore size (surface (Y)).

[0154] Example 19 A microporous membrane was obtained and the obtained separator was evaluated according to the same method as in Example 18, except that the raw materials were changed as shown in Table 5. In Table 5, "C2C4" represents an ethylene-butene random copolymerization type elastomer.

[0155] Example 20 Instead of the two-type, two-layer co-extrusion T-die, a three-type, three-layer co-extrusion T-die was installed, and film formation was performed under the same conditions as in Example 18 using the raw materials shown in Table 5, to obtain a precursor sheet with an A / C / B layer structure approximately 17 μm thick.

[0156] The obtained precursor was then placed in a dryer and annealed at 120°C for 20 minutes. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125°C without shrinking, hot stretched to 140%, and then relaxed by 15%, to obtain a separator substrate having a three-layer structure consisting of A / C / B. Here, the surface on the microporous layer (A) side had a large pore size (surface (X)), and the surface on the microporous layer (B) side had a small pore size (surface (Y)).

[0157] Comparative Examples 9 and 10 Instead of the two-kind two-layer co-extrusion T-die, a two-kind three-layer co-extrusion T-die was installed, and film formation was performed under the same conditions as in Example 18 using the raw materials shown in Table 5, to obtain a precursor sheet with an A / C / B layer structure of about 17 μm in thickness. In Table 5, "PE" indicates polyethylene (MFR (230°C) = 0.4 g / 10 min).

[0158] The obtained precursor was then placed in a dryer and annealed for 20 minutes at 120° C. The annealed precursor was then cold stretched by 20% at room temperature, and the stretched film was placed in an oven at 125° C. without shrinking and hot stretched to 140%, and then relaxed by 15% to obtain a separator substrate having a three-layer structure consisting of A / C / B.

[0159] [Table 5] [Industrial Applicability]

[0160] The separator for an electricity storage device according to the present disclosure can be suitably used as a separator for an electricity storage device, for example, a lithium ion secondary battery.

Claims

1. A substrate having a microporous layer (A) containing 70% by mass or more of polypropylene and a microporous layer (B) containing 70% by mass or more of polypropylene, a separator for an electricity storage device, wherein the area average long pore diameter of pores in the microporous layer (B) in an ND-MD cross section is 0.95 times or less the area average long pore diameter of pores in the microporous layer (A) in an ND-MD cross section.

2. The separator for an electricity storage device according to claim 1, wherein the area average long pore diameter in the ND-MD cross section of the pores in the microporous layer (B) is 0.30 to 0.90 times the area average long pore diameter in the ND-MD cross section of the pores in the microporous layer (A).

3. 3 . The separator for an electricity storage device according to claim 1 , wherein the base material has an air permeability change rate of 100% or less when heated at 140° C. for 30 minutes in air with its ends restrained.

4. The separator for an electricity storage device according to any one of claims 1 to 3, wherein the area average long pore diameter of the pores in the microporous layer (A) in an ND-MD cross section is 100 nm or more and 600 nm or less.

5. The separator for an electricity storage device according to any one of claims 1 to 4, wherein the microporous layer (A) constitutes an outermost layer on both sides of the substrate.

6. The separator for an electricity storage device according to any one of claims 1 to 5, wherein the substrate further comprises a microporous layer (C) containing 50 mass % or more of a polyolefin.

7. The separator for an electricity storage device according to claim 6, wherein the area average long pore diameter in an ND-MD cross section of the pores in the microporous layer (C) is 0.20 to 0.90 times the area average long pore diameter in an ND-MD cross section of the pores in the microporous layer (B).

8. The electricity storage device separator according to claim 6 or 7, wherein the substrate has a structure in which a microporous layer (A), a microporous layer (B), and a microporous layer (C) are laminated in this order.

9. The separator for an electricity storage device according to any one of claims 1 to 8, wherein the substrate has a structure in which a microporous layer (A), a microporous layer (B), and a microporous layer (A) are laminated in this order.

10. The surface of the substrate on the microporous layer (A) side is designated as a first porous surface (X), and the surface opposite to the first porous surface (X) is designated as a second porous surface (Y). The area average long pore diameter (S X ) is the area average long pore diameter (S Y The separator for an electricity storage device according to any one of claims 1 to 8, wherein the thickness of the separator is 1.05 to 10 times the thickness of the separator.

11. The average long hole diameter (S X The separator for an electricity storage device according to claim 10 , wherein the average particle diameter of the first and second particles is 80 nm or more and 600 nm or less.

12. The separator for an electricity storage device according to any one of claims 1 to 11, wherein the substrate has a thermal shrinkage rate in a width direction after heating at 150°C for 1 hour of -1.0% or more and 3.0% or less.

13. An electricity storage device comprising a positive electrode, a negative electrode, and the separator for an electricity storage device according to any one of claims 1 to 12.

14. The electricity storage device according to claim 13 , wherein the microporous layer (A) is disposed facing a negative electrode.

15. The power storage device according to claim 13 or 14, wherein the positive electrode contains lithium iron phosphate as a positive electrode active material.

16. A separator for an electricity storage device, comprising a substrate having a microporous layer (A) containing 70% by mass or more of polyolefin and a microporous layer (B) containing 70% by mass or more of polyolefin, the area average long pore diameter of the pores in the microporous layer (B) in the ND-MD cross section is 0.95 times or less the area average long pore diameter of the pores in the microporous layer (A) in the ND-MD cross section, The surface on the side of the microporous layer (A) is designated as a first porous surface (X), and the surface opposite to the first porous surface (X) is designated as a second porous surface (Y). The area average long pore diameter (S X ) is the area average long pore diameter (S Y ) is 1.05 times or more and 10 times or less.

17. The average long hole diameter (S X The separator for use in an electricity storage device according to claim 16 , wherein the thickness of the first and second electrodes is 80 nm or more and 600 nm or less.

18. The electricity storage device separator according to claim 16 or 17, wherein the polyolefin is polypropylene.

19. The separator for an electric storage device according to any one of claims 16 to 18, wherein the substrate has a thermal shrinkage rate in a width direction after heating at 150°C for 1 hour of -1.0% or more and 3.0% or less.

20. An electricity storage device comprising a positive electrode, a negative electrode, and the separator for an electricity storage device according to any one of claims 16 to 19.

21. The power storage device according to claim 20, wherein the first porous surface (X) is disposed opposite to a negative electrode side.

22. The power storage device according to claim 20 or 21, wherein the positive electrode contains lithium iron phosphate as a positive electrode active material.

23. A substrate having a microporous layer (A) containing 70% by mass or more of polypropylene and a microporous layer (B) containing 70% by mass or more of polypropylene, A microporous membrane, in which the area average long pore diameter of pores in the microporous layer (B) in an ND-MD cross section is 0.95 times or less the area average long pore diameter of pores in the microporous layer (A) in an ND-MD cross section.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2002319386A

  • Laminate separator, polyolefin microporous film, and separator for power storage device

    JP2016026369A

  • Porous separator for secondary battery and secondary battery using the same

    JP2017224634A

  • Improved microlayer membranes, improved battery separators, and related methods

    WO2018089748A1

  • Non-aqueous secondary battery separator and non-aqueous secondary battery

    WO2019131927A1